Relationship in Indonesia Tax Receivable Components Period 1990-2016 - Mahpudin, Endang; ., . (International Journal of Engineering and Technology, 2018)
This paper aims to analyze the revenue from the tax sector in Indonesia during the period 1990-2016. The variables in the analysis tool consist of VAT, PBB, PPH, Domestic tax, international tax, non oil tax, oil tax, other tax, bphtb, excise, cost in, export tax. The data in this study is downloaded from the website of the central body statistics and other web sites. This research uses correlation test, covariance and granger causality test. From the research conducted do explain that almost the variables of tax revenue in the meticulous have a strong linkage relationship, and mutually correlated very high, with the causality test as the tax revenue variable has a two-way relationship and partly 1 direction and mutually unrelated. So with the results in the can, be sure that the tax revenue variable there is a relationship and relevance.Â